STUDY OF THE STRUCTURE OF DISTILLED IN FRACTIONS OF A PROCESS FOR OBTAINING PISCO - Garrido S., Alberto (2008)
The purpose of this study is to know the composition of the fractions of distillates wort for the production of Pisco, two of the main grape varieties for their manufacture: Torontel and broken. The analysis was performed by the method of gas chromatography to follow the standard technique for the analysis of Peruvian Pisco. We analyzed 24 of distillate fractions obtained from two grape must Torontel and shakes, obtained by natural fermentation.The grape shakes presents a greater concentration of higher alcohols that must of torontel, but lesser amount of esters that the latter. The analysis on samples from both distillations, show a decrease in the concentration of higher alcohols and esters passes under the process of distillation, while the concentrations of acetaldehyde and methanol remained virtually constant. Considering the total volume of each fraction analyzed, all components diminish its concentration due to variation of the content of alcohol as the process progresses.